Liminal State: the Construction of Childhood in the Novels of Anna Cieplak in the Context of Polish and English YA Literature - Kocznur, Agnieszka (Porównania, 2023)
Anna Cieplak’s novels, from Ma być czysto (2016) to the most recent Rozpływam się (2021), explore the transition from childhood to adolescence, as well as the liminality of these two states. In her novels, Cieplak raises the question of at what point childhood ends. Is there a single, definite moment, an event in the life of a young person that terminates childhood? Or should we perhaps refer to a harmonious, blurred transition between states? The portrait of childhood that emerges from Cieplak’s fiction is confronted with the imagery of childhood contained in other contemporary YA books, either Polish—Agnieszka Wolny-Hamkało and Natalia Osinska—and foreign ones—Petra Dvorakova and Fiona Scarlett.